Is the more the merrier? Buyers’ onsite viewing activities and housing search outcomes - Hu, Maggie Rong; Kuang, Weida; Li, Xiaoyang; Shi, Yang (Journal of Banking & Finance, 2025)
This study investigates the underexplored role of onsite viewing activities in the housing search process. By incorporating buyer heterogeneity into the housing search model of Courant (1978), we show that buyers with higher private valuations tend to view more properties onsite and ultimately pay higher prices. Utilising a proprietary dataset from the largest real estate agency in Beijing, our analysis reveals that increased onsite viewings significantly enhance both the likelihood of a transaction and the final purchase price. We establish causality by employing an instrumental variable approach that leverages exogenous variations in heavy pollution and rainfall, which hinder buyers’ ability to conduct onsite house viewings. More intensive onsite viewings raise transaction price as they reveal a buyer’s higher private valuation to the seller. Besides, onsite viewings also function through reducing information asymmetry and improving match quality.